Analisa Pengaruh Pengeluaran Pemerintah di Sektor Pendidikan dan Kesehatan Terhadap Indeks Pembangunan Provinsi Kalimantan Selatan - Nor, Muhammad; Nasruddin (PPJP ULM, 2019)
This research was conducted to learn and analyze the impact of government expenditure on the education sector and health sector on the human development index of South Kalimantan Province. This research uses a panel in five years, from 2013 to 2017. The data processing is done using the fixed-effect model (FEM) method. This approach is a regression technique that produces a constant value or different equation intercept for each cross-section fixed in time series. The generalization process on the fixed effect approach is done by entering the dummy variable into the regression equation that made a difference in the intercept value. This research proved a significant correlation between government expenditure on the education and health sectors and the human development index in South Kalimantan Province. However, the impact of government expenditures on the education sector is negative, which means that the government expenditure on the education sector will decrease the human development index in the Province of South Kalimantan. However, the government expenditures on the health sector are significant and positive, which means that the government expenditure on the health sector will raise the human development index in South Kalimantan Province. The result was based on a t-test.